Formulation of a cosmetic cream using novel extracts of cashew nut shell from Colombian varieties of Anacardium occidentale: chemical characterization and basic product formulation (2022)
The management of cashew nut residues in Vichada, Colombia is a concern of local farmers. Large quantities of cashew nut shells are produced, nevertheless, this residue is not edible, so alternatives for its valorization must be addressed. Therefore, the objective of this study was to use cashew nut shells from Vichada for the extraction of value-added antioxidant phenolic compounds using non-conventional extraction techniques and to evaluate their possible use in the formulation of a moisturizing cosmetic cream. For this purpose, supercritical extraction with carbon dioxide and assisted by ethanol, extraction using subcritical water, and Soxhlet extraction were used to recover antioxidant extract. Then, they were characterized by chromatography to determine the content of furans, sugars, and organic acids. Total phenol content and antioxidant activity were determined by spectrophotometry. Additionally, the cytotoxicity of the extracts was determined. Supercritical extraction showed to be the most selective operation for the recovery of phenolic compounds with a concentration of 134 ± 4.58 mg/g, and antioxidant activity on DPPH of 4.55 ± 0.09 Tes/mL, being the highest of all the extracts evaluated. Soxhlet extraction and extraction with subcritical water extracted sugars and organic acids, in addition to phenolic compounds. The extract obtained with the supercritical fluid was the only one that did not show a cytotoxic effect, so it was added to the cream formulation. The cream with cashew extract showed good stability, and the test results were similar when compared to a commercial cream. Cashew nut shell extracts can be used in the formulation of cosmetic creams due to their antioxidant activity, and non-conventional extraction techniques to obtain natural compounds have a great perspective on the valorization of natural residues.